Solving the puzzle? An innovation mode perspective on lagging regions - Tobias Hädrich; Leonie Reher; Jörg Thomä (Volkswirtschaftliches Institut für Mittelstand und Handwerk an der Universität Göttingen (ifh), 2023)
The promotion of innovation-driven development in lagging regions is currently on the regional policy agenda, so a sound understanding of how learning and innovation can be successful under the conditions there is crucial. In this context, this paper demonstrates the potential of an innovation mode approach at the micro level of regional innovation systems. Based on a conceptual framework on the relationship between knowledge bases and innovation modes in the field of regional development, a systematic literature review is used to analyse whether this potential has already been exploited in previous innovation studies on lagging regions. The results show that some important steps have already been taken in this direction. However, the potential gain in terms of insights has so far only been realised to a limited extent. Against this background, the authors formulate several avenues for future research on firm-level innovation modes in lagging regions.
Keywords: O18; O30; O38; R11; 330; Regional innovation; STI innovation mode; DUI innovation mode; Lagging regions; Systematic literature review